Effect of Laser Photocoagulation and Bevacizumab Intravitreal in Proliferative Diabetic Retinopathy - Lanny, Lanny; Lucky, Lucky (The International Journal of Medical Science and Health Research, 2024)
Background: The literature on the management of proliferative diabetic retinopathy (PDR) has evolved significantly over the past decade, particularly with the introduction of anti-vascular endothelial growth factor (anti-VEGF) therapies alongside traditional laser photocoagulation techniques. Literature Review: The literature on the management of proliferative diabetic retinopathy (PDR) highlights a significant evolution in treatment strategies, particularly with the integration of anti-VEGF therapies alongside traditional laser photocoagulation. The foundational work by Arevalo (2013) establishes intravitreal bevacizumab as an effective treatment for retinal and iris neovascularization, suggesting its potential as an alternative or adjunctive therapy to conventional methods. This study emphasizes the necessity of continuous monitoring and the possibility of recurrence of neovascularization, reinforcing the importance of laser photocoagulation as a cornerstone in PDR management. Conclusion: In conclusion, the literature reflects a dynamic interplay between traditional laser therapies and innovative pharmacological approaches in the management of PDR. There is a clear trend towards integrative strategies that aim to enhance patient outcomes, emphasizing the importance of personalized treatment plans that consider both the efficacy and safety of available interventions.